PkM MESIN PEMOTONG TEMPE BAGI KELOMPOK USAHA PENGRAJIN KERIPIK TEMPE PELANGI - Ariyanto Ariyanto; Eko Yudo (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
Tempe is a typical Indonesian food with various preparations. One of the products is tempe chips, which are also home-made. The purpose of applying technology for home processing for partners is to improve the quality and production capacity of tempe chips. The results of the survey on partners making tempeh chips, it was found that the problems that occurred in partners were that the process of cutting tempeh was still manual by using a kitchen knife to cut or slice tempeh. So it takes a long time and the results of the slices or pieces of tempeh produce thin and thick dissimilarities of tempeh pieces. The solution given is the technology of cutting or slicing tempeh to make it easier to cut tempeh with the same results from thickness and thinness. The cutting results obtained are an average of 2.58 seconds/cut with a thickness of 1 mm having a texture that is not broken/cracked. In the process of producing tempeh chips, the partner's business increased by 69%.